What we know about antibiotics prescribed by dentists in a Brazilian southeastern state - Jacqueline Silva SANTOS; Alex Júnio Silva da CRUZ; Cristina Mariano RUAS; Edmilson Antônio PEREIRA JÚNIOR; Flávio de Freitas MATTOS; R. Monina KLEVENS; Mauro Henrique Nogueira Guimarães ABREU (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The objective of this study was to analyze possible associations between antibiotic dental prescriptions in the public health service, health service characteristics, and social characteristics of the municipalities. Using the register of dispensing in the public health service of a state in the Southeast region of Brazil, in 2017 we analyzed patterns of antibiotic prescriptions by dentists. Data were obtained from the Integrated Pharmaceutical Services Management System (SIGAF, in Portuguese). The outcome variable was the number of Daily Defined Doses (DDD) per 1,000 residents/year in each municipality. CART (Classification and Regression Tree) technique was used to determine the influence of the following variables: populational social characteristics (Human Development Index, Gini Index, the proportion of rural population and proportion of families benefiting from the Bolsa Família Program) and oral health services characteristics (access to individual dental care, number of dentists and oral health teams per 1,000 residents, and percentage of preventive and restorative individual dental procedures. Data analysis was performed using IBM SPSS Statistics 21.0. Antibiotics were the medications most prescribed by dentists in the public health service, with penicillin being the most frequently prescribed class. The average DDD/1,000 residents/year for the 421 municipalities surveyed was 96.54 (range 0.008 and 619.660). Select factors were associated with antibiotic prescriptions including access to individual dental care (Adjusted p-value ≤0.001), a number of oral health teams/1,000 inhabitants (Adjusted p-value=0.001), and Gini Index (Adjusted p-value = 0.046). Access to oral health services and inequality were associated with the use of antibiotics.